Discrimination, work stress, and psychological well-being in LGBTI workers in Spain - Moya, Miguel; Moya-Garófano, Alba ([Madrid] : Colegio Oficial de Psicólogos de Madrid, 2020)
Discrimination and prejudice against LGBTI people in Spain are much lower than they used to be; however, negative attitudes towards them may still persist. The purpose of this study was to analyze whether LGBTI individuals perceive the existence of prejudice or discrimination due to their sexual orientation in the workplace. To assess these perceptions in relative terms, we compared them with those of heterosexual individuals. We also analyzed whether perceived discrimination was associated with work stress, the presence of common mental disorders, and depression. Results revealed that LGBTI employees reported experiencing greater discrimination in the workplace because of their sexual orientation, which in turn led to a greater incidence of work stress, mental disorders, and depression. Our findings confirm that job discrimination against LGBTI people is still present, along with some of its harmful consequences, and highlight the need for interventions to reduce prejudice against LGBTI persons in the workplace.
Descripción basada en Psychosocial Intervention, vol. 29, núm. 2 (may 2020), P. 93-101.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Depresión.; Estrés laboral; Homofobia; LGTB+.; Trastornos mentales; Artículos.